Multi G -cyclic Operators are G-cyclic - Jamil, Zeana Z. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
Paris proved in 2001 Herrero's conjectured "that every multi-hypercyclic (multi- supercyclic) operator on a Hilbert space is in fact hypercyclic (supercyclic) In this paper we study this conjectured in many cases of operators between hypercyclic operators and supercyclic operators. And we proved that multi G-cyclic operator is G-cyclic operator.